Is mental health contagious ? Depression, anxiety, stress and burnout among Mental health professionals in Sudan - Iyas Ahmed Abdelhadi; Omer A. Mohammed; Shaza K. Babikir; Eman Abdulkarim Mohammed Abdulkarim Bedri; Alaa Ahmed Abdelhadi (BMC Psychiatry, 2025)
Abstract Background Mental health professionals are more likely to experience mental health problems due to their work environment,Poor management of this can lead to job dissatisfaction, low organizational commitment and high turnover. The goal of this cross-sectional study is to evaluate the mental health of health care professionals working in Khartoum state psychiatric hospitals in order to comprehend effective coping strategies. Methods Data was collected through both online and paper questionnaires from a sample of 164 mental health professionals working in the major mental health institutions in Sudan’s Capital state. The study examined variables including sociodemographic characteristics, stress, personal burnout, depression and anxiety. Using Both English and Arabic versions of DASS-21 and CBI scales. Results The study examined 164 mental health workers, primarily women, with an average age of 35.8 years and 7.3 years of experience. The participants were mostly married and worked at private institutions. Psychiatric registrars and psychologists were the most common professions. Results indicated that the DASS-21 stress subscale had the highest mean score pointing to significant stress levels among participants. While the majority reported no depression or anxiety. some experienced severe forms of these conditions. Personal burnout was highest on the CBI subscales. Age and experience were negatively associated with depression, anxiety, and work-related burnout, suggesting that older and more experienced professionals had lower levels of these issues. All DASS subscales were significantly correlated with higher degrees of burnout, emphasizing the strong link between psychological distress and burnout. These findings highlight the need for effective strategies to support the mental health and well-being of mental health professionals. Conclusion The study suggests that mental health professionals in Sudan are experiencing relatively high levels of depression, stress, anxiety, and burnout. This highlights the need for effective strategies to support the mental well-being of healthcare professionals in this setting.